Lost foam casting of LM6-Al-Si cast alloy - A. Asmael, Mohammed Bsher (2009)
In the present research, experimental investigation of an investigation of lost foam casting of LM6-Al-Si cast alloy has been conducted. The investigation has as main objectives to investigate the effect of pouring temperature and melt treatment by addition of grain refiner on the microstructure and mechanical properties of lost foam castings of the LA-Si alloy. Castings in the shape of step-like with five sections were produced mainly using a foam density of 20 kg/m³ and pouring was made at five different temperatures of 700,720,740,760,780oC with and without the presence of AlTiB grain refiner in the melt. The different pouring temperatures would permit obtaining castings at different cooling rates. The results obtained showed that pouring temperature has a significant influence on the quality as well as microstructure of lost foam casting of LM6- Al-Si alloy. Lower pouring temperature provides finer microstructure and high hardness and that faster cooling rate produced either by lower pouring temperature or thinner section would results in enhanced hardness. However, the addition of AlTiB as grain refiner did not affect the castings produced significantly whether in terms casting quality or microstructure.